High Frequency of Previous Abuse and Missed Diagnoses Prior to Abusive Head Trauma: A Consecutive Case Series of 100 Forensic Examinations. (22nd June 2020) - Laurent‐Vannier, Anne; Bernard, Jonathan Y.; Chevignard, Mathilde
Abstract : This study describes the frequency of signs and symptoms of abuse and missed diagnoses prior to the diagnosis of abusive head trauma (AHT) in infants. Data were from a retrospective observational study of 100 consecutive cases of infants diagnosed with AHT over a seven‐year period. The most frequent symptom leading to the diagnosis was a loss of consciousness (68%) that always occurred inside a home (parents' or nanny's), never outside. Diagnosis was established using criteria based on the child's lesions and the alleged history. Lesions leading to diagnosis were described: 99 per cent had multifocal subdural haematoma (SDH) located in four areas including lateral space, interhemispheric, tentorium cerebelli and vertex; 60 per cent had a rupture of bridging veins. Previous abuse was found in 79 per cent of cases, of whom 75 per cent underwent medical consultations that did not result in a diagnosis of abuse. The main signs and symptoms of previous abuse were repeated vomiting without fever or diarrhoea (62%), abnormal head circumference increase (49%) and bruises (38%). These results suggest a higher frequency of repeated abuse than previous studies and highlight the great challenges most professionals encounter to evoke and set the diagnosis of abuse. 'This study describes the frequency of signs and symptoms of abuse and missed diagnoses prior to the diagnosis of abusive head trauma (AHT) in infants' Key Practitioner Messages: Prior signs and symptoms suggestive of abuse are particularly frequent in infants diagnosed with AHT. Abuse must be detected as early as possible in order to avoid recurrences. Diagnostic criteria, based on clinical history and lesions including multifocal subdural haematoma, rupture of bridging veins, retinal haemorrhages, and spinal cord injury have been defined to enable diagnosis of AHT.